BUMDes Berbadan Hukum dan Kemandirian Ekonomi Desa: Analisis Yuridis atas Tantangan dan Peluang Implementasi Regulasi - Kasmawati; Siswanto, Heni; Muhtadi; Putri, Ria Wierma; Silviana, Ria (Fakultas Hukum Universitas Riau, 2025)
This study aims to analyze the role of village-owned enterprises (BUMDes) with legal entity status in driving village economic independence and supporting sustainable national development. The research focuses on identifying challenges faced by BUMDes, including regulatory complexity, administrative constraints, limited legal literacy, and weak governance practices, while exploring opportunities arising from their formal legal recognition. Using a qualitative normative approach, the analysis highlights how legal entity status strengthens institutional legitimacy, facilitates access to financing, encourages business partnerships, and promotes diversification of economic activities at the village level. Findings show that despite significant opportunities, implementation remains suboptimal due to structural, managerial, and technological barriers. The study emphasizes the need for capacity-building programs, harmonization of regulations, and stronger collaboration between government, academia, and local institutions to improve governance quality and maximize BUMDes’ potential. Strengthening BUMDes as legal entities can enhance community participation, create sustainable economic growth, and position villages as strategic actors within the broader national economy.